(untitled) (Konferensiyalar | Conferences, 2024)
In the contemporary landscape of education, the emphasis on developing professional communicative competence among students has become increasingly paramount. Particularly in the realm of teaching English as a second language, educators are continuously seeking innovative methodologies to cultivate effective communication skills in their students. One such approach gaining traction is Problem-Based Learning (PBL) technology, which offers a dynamic platform for enhancing linguistic proficiency while addressing real-world challenges. In this article, some key aspects of how Problem-Based Learning technology contributes to improve the professional communicative competence of students in teaching English are discussed.